2019
DOI: 10.1371/journal.pone.0222338
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical parameters for Chinese rhesus macaque

Abstract: Rhesus macaque is an important animal model in biomedical research, especially human disease, developmental, translational, and pre-clinical research. Blood physiological and biochemical parameters are important markers for physiology, pathology, and toxicology research. However, these parameters have not been systematically reported for Chinese rhesus macaques. To characterize the reference for these parameters, this study collected 1805 Chinese rhesus macaques living in Southwestern China. A total of 24 bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
4
15
0
Order By: Relevance
“…In the present study, higher triglyceride levels were found in older individuals compared to younger monkeys both before and after the dietary change. Similar age-effects have been reported in other studies with both long-tailed macaques and rhesus macaques [ 42 , 43 , 59 , 60 ]. Possibly, no significant effect of dietary change on triglyceride levels was found because the effect of dietary change was counteracted by an age-effect.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, higher triglyceride levels were found in older individuals compared to younger monkeys both before and after the dietary change. Similar age-effects have been reported in other studies with both long-tailed macaques and rhesus macaques [ 42 , 43 , 59 , 60 ]. Possibly, no significant effect of dietary change on triglyceride levels was found because the effect of dietary change was counteracted by an age-effect.…”
Section: Discussionsupporting
confidence: 87%
“…5 E– 5 K), indicating that 25HC will not cause additional toxicity to the kidney and heart. Compared to the ART-only group, the ratio of AST/ALT in RMs of 25HC+ART group was within the normal range (Yu et al 2019 ), although there was a higher concentration of aspartate aminotransferase (AST) in the 25HC+ART group (Fig. 5 F), suggesting that 25HC will not cause additional toxicity to liver.…”
Section: Resultsmentioning
confidence: 87%
“…H , Comparison of red blood cell counts to corresponding reports from the literature. Labeling of x -axis (SC68, …, KL19) refers to Stanley and Cramer (1968) , Rosenblum and Coulston (1981) , Kessler and Rawlins (1983) , Bennett et al (1992) , Fernie et al (1994) , Buchl and Howard (1997) , Hom et al (1999) , Smucny et al (2001) , Andrade et al (2004) , Chen et al (2009) , Didier et al (2012) , Koo et al (2019) , and Yu et al (2019) , in that order. “Own” refers to data from present study, as shown in G .…”
Section: Resultsmentioning
confidence: 99%
“…For testing effects over the entirety of blood values, false positives were controlled by setting the FDR criterion to α = 0.1. Literature values for comparison were obtained from Stanley and Cramer (1968) , Rosenblum and Coulston (1981) , Kessler and Rawlins (1983) , Bennett et al (1992) , Fernie et al (1994) , Buchl and Howard (1997) , Hom et al (1999) , Smucny et al (2001) , Andrade et al (2004) , Chen et al (2009) , Didier et al (2012) , Koo et al (2019) , and Yu et al (2019) . If a given paper reported blood values separately for male and female animals, we only considered males.…”
Section: Methodsmentioning
confidence: 99%